Do the health benefits of cycling outweigh the risks? - Hartog, Jeroen Johan de; Boogaard, Hanna; Nijland, Hans; Hoek, Gerard (National Institute of Environmental Health Sciences, 2010)
Although from a societal point of view a modal shift from car to bicycle may have beneficial health effects due to decreased air pollution emissions, decreased greenhouse gas emissions and increased levels of physical activity, for the shifting individual adverse health effects such as higher exposure to air pollution and risk of a traffic accident may prevail. This paper describes whether the health benefits from the increased physical activity of a modal shift for urban commutes outweigh the health risks. The literature for air pollution, traffic accidents and physical activity were summarized using systematic reviews supplemented with recent key studies. The impact on all-cause mortality when 500,000 people would make a transition from car to bicycle for short trips on a daily basis in the Netherlands was quantified. Mortality impacts in life years gained or lost making use of life table calculations were expressed. For the individuals who shift from car to bicycle, beneficial effects of increased physical activity are substantially larger (3 - 14 months gained) than the potential mortality effect of increased inhaled air pollution doses (0.8 - 40 days lost) and the increase in traffic accidents (5 - 9 days lost) were estimated . Societal benefits are even larger due to a modest reduction in air pollution and greenhouse gas emissions and traffic, accidents. On average, the estimated health benefits of cycling were substantially larger than the risks relative to car driving for individuals shifting mode of transport.
Keywords: Fahrradverkehr; Vergleich; Umweltschutz; Verkehrsunfall; Gesundheitsschutz; Verkehrsmittelwahl; Verkehrsverhalten; Individualverkehr; Fahrradnutzung